2020
DOI: 10.1111/imm.13270
|View full text |Cite
|
Sign up to set email alerts
|

Why do intestinal epithelial cells express MHC class II?

Abstract: Summary Intestinal epithelial cells (IECs) constitute the border between the vast antigen load present in the intestinal lumen and the mucosal immune compartment. Their ability to express antigen processing and presentation machinery evokes the question whether IECs function as non‐conventional antigen‐presenting cells. Major histocompatibility complex (MHC) class II expression by non‐haematopoietic cells, such as IECs, is tightly regulated by the class II transactivator (CIITA) and is classically induced by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 91 publications
(151 reference statements)
4
33
0
Order By: Relevance
“…The most striking IFN-γ-induced change to the cIECs was the continued expression of MHCII antigen presentation proteins at 48 DPI. While MHCII molecules are constitutively expressed in small intestinal IECs (siIECs), cIECs have been shown to express MHCII in response to IFN-γ ( 42 ), and we find that Ifn γ −/− mice do not show an increase in MHCII + cIECs during or after C. rodentium infection, confirming that IFN-γ is essential in this context. The role of cIEC MHCII expression during and after infection is not well understood.…”
Section: Discussionsupporting
confidence: 54%
“…The most striking IFN-γ-induced change to the cIECs was the continued expression of MHCII antigen presentation proteins at 48 DPI. While MHCII molecules are constitutively expressed in small intestinal IECs (siIECs), cIECs have been shown to express MHCII in response to IFN-γ ( 42 ), and we find that Ifn γ −/− mice do not show an increase in MHCII + cIECs during or after C. rodentium infection, confirming that IFN-γ is essential in this context. The role of cIEC MHCII expression during and after infection is not well understood.…”
Section: Discussionsupporting
confidence: 54%
“…The classic pathway of antigen recognition and presentation involves the sampling of the gut lumen by dendritic cells (DC) followed by internalization and presentation of antigens via MHCII to T cells. However, there is also a surprisingly significant role for MHCII expressed on IECs in the gut, which seems to be attributed to ISC Lgr5+ cells which act as nonconventional antigen-presenting cells and orchestrate epithelium structure both during homeostasis and infections [ 68 ]. These cells are sensitive to cytokines and are promoted towards renewal, or differentiation to Paneth cells or TCs upon exposure to Th reg , Th 1 , and Th 2 (and their cytokines), respectively [ 69 ].…”
Section: Helminth Recognitionmentioning
confidence: 99%
“…35 Although the roles MHC II plays on epithelial cells in the lungs and in the intestinal tract are still being characterized, studies have shown that epithelial cells can act as aAPCs under both normal conditions and inflammatory conditions. 36,37 As these findings have been extensively discussed elsewhere, 36,37 and evidence on antigen presentation by epithelial cells in the TME is lacking, we have focused instead on the conditions under which MHC II expression on epithelial cells is regulated in inflammatory settings, the TME being one such setting.…”
Section: Epithelial Cellsmentioning
confidence: 99%